2021
DOI: 10.1101/2021.01.31.428969
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trajectory reconstruction identifies dysregulation of perinatal maturation programs in pluripotent stem cell-derived cardiomyocytes

Abstract: A primary limitation in the clinical application of pluripotent stem cell derived cardiomyocytes (PSC-CMs) is the failure of these cells to achieve full functional maturity. In vivo, cardiomyocytes undergo numerous adaptive changes during perinatal maturation. By contrast, PSC-CMs fail to fully undergo these developmental processes, instead remaining arrested at an embryonic stage of maturation. To date, however, the precise mechanisms by which directed differentiation differs from endogenous development, lead… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…We assessed general pathways enriched in NRVM and iPSC-CM by gene ontology, which further supports our findings that iPSC-CM are in a maturation pseudotime between P7 and P14 CM, whereas NRVM are in P0 pseudotime, with ensuing distinct transcriptomic profiles. Our results are corroborated by a recent single-cell study characterizing the maturation of iPSC-CM and P0-P84 CM 74 that also suggested an overlap between iPSC-CM and P11-P14 CM.…”
Section: Igfbp-3 Network and Modulessupporting
confidence: 89%
“…We assessed general pathways enriched in NRVM and iPSC-CM by gene ontology, which further supports our findings that iPSC-CM are in a maturation pseudotime between P7 and P14 CM, whereas NRVM are in P0 pseudotime, with ensuing distinct transcriptomic profiles. Our results are corroborated by a recent single-cell study characterizing the maturation of iPSC-CM and P0-P84 CM 74 that also suggested an overlap between iPSC-CM and P11-P14 CM.…”
Section: Igfbp-3 Network and Modulessupporting
confidence: 89%
“…The data set can be found on the GEO database using accession GSE137524. Data set 3: Cardiomyocyte data set from the study of [ 9 ]. The data were downloaded from the GEO database using accession GSE164591.…”
Section: Methodsmentioning
confidence: 99%
“…Data set 2 is from the human SCC6 cell line treated with cetuximab and PBS (control) [ 8 ]. Data set 3 is from differentiating mouse cardiomyocytes across fifteen real timepoints [ 9 ]. In all three cases, we set out to examine whether the top-ranking gene candidates reported by scInTime will be aligned well with those obtained from functional studies, in which corresponding master regulators are reported.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent study, NrF2 encoded by the NFE2L2 gene is highly expressed during the early stages of mouse in vivo CM differentiation which aligns well with its role in enhancing mitochondrial respiration as part of early CM metabolic maturation. However, the time-course of NFE2L2 activity in vivo is not recapitulated in in vitro PSC-CM differentiation and was posited to be one of the key factors responsible for maturation arrest of in vitro CM differentiation ( 93 ). It is complicated to interpret the significance of NFE2L2 stage-specific activity in CM maturation; however, increased ROS levels is an important inducer of DNA damage response which is implicated in CM proliferation arrest as part of CM maturation process ( 94 ).…”
Section: Signaling Pathways Potentially Associated With Human Induced...mentioning
confidence: 99%
“…The results of recent studies suggest that current maturation protocols produce CMs that are still far from the adult CM state; this failure is partly due to the fact that none of the methods are sufficient to fully activate all major TFs involved in CM maturation ( 93 ). Another major limitation of current methodologies is the absence of a global metric for the assessment of the degree of CM maturation reported by different studies.…”
Section: Transcriptional Regulation Of Human Induced Pluripotent Stem...mentioning
confidence: 99%